Induksi Akar pada Setek Batang Aglaonema sp. Var Siam Aurora dengan Pemberian IBA dan NAA - Amalia Hartias Anggraini; Desi Maulida; Lisa Erfa; Rizka Novi Sesanti; Yeni Yeni; Sekar Utami Putri (Politeknik Negeri Lampung, 2023)
Stem cutting propagation is commonly used to vegetative propagated of Aglaonema sp, however the growing roots has not been much growth. Nevertheless, the shoots that grow only one to three buds with the length of time shoots and roots appear is about 50-75 days after cuttings. It is all depends on the genotype of the Aglaonema sp. The aims of this study was to (i) determine the effect of IBA and NAA concentration in inducing roots of Aglaonema sp. Var Siam Aurora stem cuttings; (ii) to determine the interaction of IBA and NAA treatments to inducing roots of Aglaonema sp. Var Siam Aurora; (iii) determine the best combination of IBA and NAA to inducing roots of Aglaonema sp. Var Siam Aurora. The experimental design was Randomized Block Design (RBD) Factorial with the first factor is the IBA concentration; 0 mg.l-1(I0) and 1000 mg.l-1(I1). The second factor is NAA concentration; 0 mg.l-1(N0), 500 mg.l-1 (N1), 1000 mg.l-1 (N2), 1.500 mg.l-1 (N3)and 2000 mg.l-1 (N4) and resulting 10 combination treatments of IBA and NAA. The data was conducted with analysis of variance and followed by BNT test at 5% and the variable observed were root length, number of roots, first time of roots growth, first time of buds growth, the percentage of cutting stem. The result showed that the combination of IBA and NAA 1000 mg.l-1 give significant effect to inducing cutting stem of Aglaonema sp. Var Siam Aurora.